The conception of man among the Incas - Hernández Astete, Francisco (2010)
The notion that pre-conquest Andean people believed that they were composed of a body and a soul – and that the soul was what distinguished them from other beings – has been widely accepted since the sixteenth century. This article disputes this idea and establishes the basis for a more accurate understanding of the Andean conception of humanity. The misunderstanding of Andean conceptions began with the Àrst western informants on the Andean world. These Christians, born in Europe at the end of the fifteenth century, themselves believed that all humans were composed of body and soul. Having concluded that Andean people had rational souls and hence did not belong to the monstrous races of the western imagination, Spanish evangelists initiated a campaign of evangelization designed to save American souls. Their preparation of Andean people for Christian salvation included a long process of “introducing” aboriginal souls.